Sialic Acid Is Required for Neuronal Inhibition by Soluble MAG but not for Membrane Bound MAG - Al-Bashir, Najat; Mellado, Wilfredo; Filbin, Marie T. (Frontiers in Molecular Neuroscience, 2016)
Myelin-Associated Glycoprotein (MAG), a major inhibitor of axonal growth, is a member of the immunoglobulin (Ig) super-family. Importantly, MAG (also known as Siglec-4) is a member of the Siglec family of proteins (sialic acid-binding, immunoglobulin-like lectins), MAG binds to complex gangliosides, specifically GD1a and/or GT1b. Therefore, it has been proposed as neuronal receptors for MAG inhibitory effect of axonal growth. Previously, we showed that MAG binds sialic acid through domain 1 at Arg118 and is able to inhibit axonal growth through domain 5.We developed a neurite outgrowth assay (NOG), in which both wild type MAG and mutated MAG (MAG Arg118) are expressed on cells. In addition we also developed a soluble form NOG in which we utilized soluble MAG-Fc and mutated MAG (Arg118-Fc. Only MAG-Fc is able to inhibit neurite outgrowth, but not mutated MAG (Arg118)-Fc that has been mutated at its sialic acid binding site. However, both forms of membrane bound MAG- and MAG (Arg118)- expressing cells still inhibit neurite outgrowth. Here, we review various results from different groups regarding MAG’s inhibition of axonal growth. Also, we propose a model in which the sialic acid binding is not necessary for the inhibition induced by the membrane form of MAG, but it is necessary for the soluble form of MAG. This finding highlights the importance of understanding the different mechanisms by which MAG inhibits neurite outgrowth in both the soluble fragmented form and the membrane-bound form in myelin debris following CNS damage